Friendship : Development, Ecology, and Evolution of a Relationship - Hruschka, Daniel J., 1972- (Book collections on Project MUSE., 2010)
Friends-they are generous and cooperative with each other in ways that appear to defy standard evolutionary expectations, frequently sacrificing for one another without concern for past behaviors or future consequences. In this fascinating multidisciplinary study, Daniel J. Hruschka synthesizes an array of cross-cultural, experimental, and ethnographic data to understand the broad meaning of friendship, how it develops, how it interfaces with kinship and romantic relationships, and how it differs from place to place. Hruschka argues that friendship is a special form of reciprocal altruism base.